Market Structure of Nuclear Power Industry and Incentives of Major Firms - Nam, Il Chong (KDI School of Public Policy and Management, 2013)
This paper analyzes the nuclear power industry of Korea from the perspective of competition. It is first such attempt as all previous works on the economics of nuclear power industry in Korea have been focused exclusively on the comparison of total costs of generating electricity of nuclear power plants and other fuel types. We found out that nuclear power industry in Korea is characterized by successive monopolies, dominance of KEPCO in terms of the ownership of major firms, and low degree of accountability and transparency in the management of SOEs. We also found out that the government, in particular the line ministry of the nuclear and electricity industries, plays a crucial role in determining the market structure and governance of firms and hence the outcome of competition in the market. Vertical integration of the monopolies in fuel fabrication, nuclear power generation, and waste treatment and disposal are likely to work as an entry barrier to each of the three horizontal markets and reduce competition in the long run. Vertical integration of these subsidiaries of KEPCO coupled with the unusual governance structure imposed on them by the government are also likely to lower efficiency in the relevant markets. The fact that KEPCO is the monopsonist in the retail stage of the electricity industry makes it more difficult to induce effective competition in each of the horizontal stages that constitute the nuclear power industry. It is too early to draw a definite conclusion about the concrete form of the market structure and the ownership and governance structure of KEPCO and its subsidiaries that will induce an efficient outcome. However, based on the findings of this paper, it is clear that a change in the policy of the Korean government that unbundles various horizontal stages, lowers of entry barriers, and strengthens the profit incentives of SOEs as well as transparency and accountability of them will improve the efficiency of the industry and ultimately increase welfare of consumers of electricity in Korea.